IRB challenges in multisite studies: A case report and commentary from the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS-TILDA). - Mc Carron, Mary; Haigh, Margaret; Mc Causland, Darren (My University, 2024)
A shift from single to multi-site health studies enabled a range of research benefits including faster recruitment of larger and more diverse samples; increased statistical power, greater rigour, generalisability, and external reliability; and increased likelihood of impacting policy and clinical practice. However, ethical review of multi-site studies by Institutional Review Boards (IRBs) raises specific challenges compared with single site studies, with requirements to apply to multiple local IRBs increasing the burden on research, possibly endangering the integrity of the research process or inhibiting development of multi-site studies. The option of a single centralised IRB may offer a clearer, more consistent and efficient review process. This study presents a case report and commentary from 15 years engaging with IRBs in multiple sites in Ireland by the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS-TILDA). It examines the ethics review process for IDS-TILDA through its first four waves. While the majority of 48 IRBs granted ethical approval within 13 weeks, six IRBs took 21–47 weeks to approve, leading to delays in data collection of up to 11 months. Despite additional review time, no changes were required to the study protocol. Therefore, a critical impact of the process was the delay in starting data collection within a small number of organisations, and reduced involvement in the study for one organisation. The ethical review process with multiple IRBs increased the degree of complexity of the process, with added bureaucracy and far greater communication required across 48 IRBs, substantially adding to the resource commitment for the review process. The relatively quick approval from the majority of IRBs was partially a result of the longitudinal study building relationships with organisations throughout multiple waves. That other health studies may not accrue this benefit supports calls for a single IRB system for multi-site health studies.
PUBLISHED
Keywords: research ethics, health research, multi-site study, institutional review board (IRB); Ageing